Use of Information Technology for Communication and Learning in Secondary School Students with a Hearing Disability - Theeratorn Lersilp; Suchitporn Lersilp (MDPI AG, 2019)
Information technology (IT) is important to meet the needs of students with a hearing disability in special Thai school settings. The aim of this paper was to research the use and opinion of IT for communication and learning from students with a hearing disability in schools for the deaf. The IT in this study included information devices such as mobile phones, smartphones, and tablets. This study used the stratified random sampling method for enrolling its participants. Data collected from 192 students with a hearing disability using a self-administered questionnaires. Results found that most of these students knew about chat applications, for example, Line, Facebook, Messenger and face-to-face conversation apps. Furthermore, most of these students contacted people with hearing problems by sending messages through Facebook, Line and face-to-face applications. The main reasons why they used IT was for convenience and general conversation. A study of opinions on the use of IT by students with a hearing disability found that most of them agreed that IT equipment contributed to their participation in various activities, including conversations with their relatives and friends on social networking. Conclusion and discussions were included.